A biodegradable and fluorescent nanovehicle with enhanced selective uptake by tumor cells. Issue 36 (6th August 2015) - An, Jinxia; Dai, Xiaomei; Zhao, Yu; Guo, Qianqian; Wu, Zhongming; Zhang, Xinge; Li, Chaoxing
Abstract : The tumor-targeted drug delivery system, DOX@LA-pDAGEA/pPEGA- b -p(DMDEA- co -BADS), with reduction- and pH-dependent degradation and fluorescence imaging function displayed an enhanced anticancer effect. Abstract : To improve the pharmacokinetic and pharmacodynamic profiles of clinical anticancer drugs for cancer therapy, the development of effective drug delivery systems with precise biological functions is critically required. In the current study, we developed a PEGylated and core-cross-linked polymeric nanovehicle, LA-pDAGEA/pPEGA- b -p(DMDEA- co -BADS), with reduction- and pH-dependent degradation and fluorescence imaging function for tumor-targeted delivery of hydrophobic drugs. The multifunctional copolymers were synthesized using RAFT polymerization. By utilizing the intrinsic fluorescence of nanovehicles resulting from the boron–dipyrromethene dye-conjugated chain transfer agent (BODIPY), the cellular internalization process was exhibited. Cellular uptake and the competition inhibition assay show that the nanovehicles could be internalized into HepG2 cells via receptor-mediated endocytosis. Moreover, the drug-loaded nanovehicles were capable of significantly inhibiting cancer cell proliferation. Our newly developed multifunctional nanovehicles may thus facilitate the development of efficient drug delivery systems for application in diagnosis and therapy of cancer.